INVESTIGATING THE ROLE OF SIRT5 IN MODULATING HEPG2 CELL STIFFNESS AND ITS IMPLICATIONS FOR LIVER DISEASE - Ormantayeva, Anar (Nazarbayev University School of Sciences and Humanities, 2025)
Hepatocyte mechanics are increasingly recognized as early sentinels of metabolic liver disease, yet the molecular drivers that couple energy metabolism to cellular stiffness remain obscure. Here we interrogate the mitochondrial de-succinylase Sirtuin-5 (SIRT5) as a putative link between metabolism and mechanobiology due to its regulation of fatty-acid oxidation, redox balance, and ATP production. GFP-tagged shRNA constructs targeting the two principal SIRT5 splice variants (isoforms A and B) were transiently introduced into HepG2 cells and verified by fluorescence microscopy. Atomic-force microscopy, performed 48 h post-transfection, revealed that silencing SIRT5 softened hepatocytes rather than stiffening them: Young’s modulus fell by ~40 % after isoform A knock-down and by ~15 % after isoform B knock-down relative to scrambled controls, with GFP-negative sister cells confirming the specificity of the response. Concomitantly, CellROX assays showed a non-significant but consistent rise in reactive-oxygen species, while PrestoBlue measurements documented an acute dip followed by full recovery of metabolic viability over three days. Taken together, the data support a mechano-metabolic model in which diminished SIRT5 activity curtails mitochondrial ATP output and elevates oxidative stress, loosening actomyosin tension and thereby reducing cellular stiffness. Because hepatocyte softening precedes fibrotic matrix deposition in non-alcoholic fatty liver disease and other chronic liver disorders, our findings position SIRT5 as an upstream coordinator of both bioenergetics and biomechanical homeostasis. Targeting SIRT5 or its downstream pathways may thus offer a dual strategy to rebalance redox status and restore tissue mechanics in early liver pathology.
Keywords: SIRT5; Sirtuin 5 Histone Deacylase; hepatocyte stiffness; Atomic Force Microscopy; Young’s modulus; oxidative stress; reactive oxygen species; HepG2 cells; non-alcoholic fatty liver disease; mitochondrial bioenergetics; type of access: embargo